2010
DOI: 10.1016/j.jbiomech.2010.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The region-dependent biphasic viscoelastic properties of human temporomandibular joint discs under confined compression

Abstract: The objective of this study was to determine the biphasic viscoelastic properties of human temporomandibular joint (TMJ) discs, correlate these properties with disc biochemical composition, and examine the relationship between these properties and disc dynamic behavior in confined compression. The equilibrium aggregate modulus (H A ), hydraulic permeability (k), and dynamic modulus were examined between five disc regions. Biochemical assays were conducted to quantify the amount of water, collagen, and glycosam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
2
45
2
Order By: Relevance
“…Journal of Dental Biomechanics The collagen content of the goat TMJ disc is less than that of the previously reported porcine (68.2 ± 14.5%) and human TMJ disc (62.0 ± 11.4) [17,34]. We did validate our collagen assay with porcine samples and obtained results comparable to literature [35].…”
Section: Discussionsupporting
confidence: 71%
“…Journal of Dental Biomechanics The collagen content of the goat TMJ disc is less than that of the previously reported porcine (68.2 ± 14.5%) and human TMJ disc (62.0 ± 11.4) [17,34]. We did validate our collagen assay with porcine samples and obtained results comparable to literature [35].…”
Section: Discussionsupporting
confidence: 71%
“…The TMJ disc was considered as uncharged in this study, since biochemical studies have shown that the GAG content of human and porcine TMJ discs is very low (< 4% dry weight) compared with that of hyaline cartilage and IVD (Almarza et al, 2006;Kuo et al, 2010). For uncharged tissues in NaCl, the relative diffusivity (D/D 0 ) of NaCl is simply related to the relative conductivity by (Gu et al, 2004): where D is the mean ion diffusivity of Na + and Cl -in tissue, D 0 is the mean ion diffusivity in the bathing solution, χ is the electrical conductivity of the tissue, and χ 0 is the conductivity of the bathing solution.…”
Section: Ion Diffusivity Calculationmentioning
confidence: 99%
“…Based on the Donnan equation, electroneutrality condition and van’t Hoff’s equation for tissue osmotic swelling pressure 8 , cross-region FCD generates 11 kPa of osmotic pressure in males and 6.8 kPa of osmotic pressure in females. With the reported compressive modulus of the human TMJ disc in the range of 22–70 kPa with an average of 51 kPa 15 , osmotic pressure is approximately 20% of the overall compressive modulus of the TMJ disc. In comparison, the average FCD in healthy human knee articular cartilage (0.2 mEg/g wet tissue) can generate 155 kPa osmotic pressure, which has an average compressive modulus of 700 kPa 25 .…”
Section: Discussionmentioning
confidence: 98%